Penerapan Metode Mediated Learning Experience (MLE) pada Ibu dengan Anak Usia 3-4 Tahun untuk Meningkatkan Kualitas Interaksi dalam Kegiatan Pemberian Makan - Hilda Intan Budi Permatahati; Sri Redatin Retno Pudjiati; Luh Surini Yulia Savitri (Fakultas Psikologi Universitas Tarumanagara, 2019)
Feeding is the right time for parent and child to interact. Based on elicitation, it shows that there is lack of interaction between mother and child when feeding activity. This research is aimed to improve the quality of both interaction between mother and child, and deliver education that related to food and its’ function. One of the method which can be used to increase quality of interaction when feeding activity, is Mediated Learning Experience (MLE). Mediated Learning Experience is an active interaction when parent or substitute adult modify the stimulus to improve the child’s ability. MLE method given to mothers by training. This research is one group pre-test and post-test design research. Measurement in this study used Wilcoxon Signed-Ranks Test. The result on pre-test – post-test 1 shows that p = 0,012 (p < 0,05) or can be said that there is a significant difference between the quality of parent and child interaction while feeding activity before and after being given MLE training. Then, post-test 1 – post-test 2 shows p = 0,167 (p > 0,05) or can be said that there is no significant difference between the quality of parent and child interaction while feeding activity on post-test 1 and post-test2.